AN INTRODUCTION TO ANATOMICAL HISTOLOGICAL TERMINOLOGY: NOUNS AND THEIR GRAMMAR CATEGORIES - Yorova Sayora Karimovna ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
In this article, there is illustrated introduction to anatomic histological terminology specifically focusing on the noun and its grammar categories. It explores the determination of gender, stem foundation, vocabulary forms and declination of nouns within this domain.